2020
DOI: 10.7554/elife.58731
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of specific cortical GABAergic circuits underlie abnormal network activity in a mouse model of Down syndrome

Abstract: Down syndrome (DS) results in various degrees of cognitive deficits. In DS mouse models, recovery of behavioral and neurophysiological deficits using GABAAR antagonists led to hypothesize an excessive activity of inhibitory circuits in this condition. Nonetheless, whether over-inhibition is present in DS and whether this is due to specific alterations of distinct GABAergic circuits is unknown. In the prefrontal cortex of Ts65Dn mice (a well-established DS model), we found that the dendritic synaptic inhibitory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…The density of PV + cells across multiple cortical layers was found to be increased in Ts65Dn mice by some investigators 46 , 47 . However, Zorrilla de San Martin and collaborators 48 reported that perisomatic inhibition from PV + interneurons was unaltered in Ts65Dn mice. Instead, these investigators observed that these cells lost their classical fast-spiking phenotype and exhibited increased excitability.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The density of PV + cells across multiple cortical layers was found to be increased in Ts65Dn mice by some investigators 46 , 47 . However, Zorrilla de San Martin and collaborators 48 reported that perisomatic inhibition from PV + interneurons was unaltered in Ts65Dn mice. Instead, these investigators observed that these cells lost their classical fast-spiking phenotype and exhibited increased excitability.…”
Section: Discussionmentioning
confidence: 98%
“…Recent findings showing a delayed GABA polarity switch in the hippocampus of neonatal Ts65Dn mice suggest developmental delays in maturation of neural circuits of these animals, which in turn may contribute to the disruption of E/I balance towards inhibition in adult Ts65Dn mice 50 . In addition, Zorrilla de San Martin et al 48 reported that the dendritic inhibitory loop involving excitatory pyramidal neurons and Martinotti cells (which are somatostatin-positive interneurons that inhibit distal dendrites of excitatory pyramidal neurons) is enhanced in Ts65Dn mice 48 . Since α5-containing GABA A R mediate synaptic inhibition of pyramidal cell dendrites by Martinotti cells 51 , these findings may support previous evidence on the rescue of learning/memory deficits and synaptic plasticity deficits in Ts65Dn mice by negative allosteric modulators (NAMs) of these receptors 52 55 .…”
Section: Discussionmentioning
confidence: 99%
“…This LTP failure is largely determined by alterations in the GABAergic system ( Kleschevnikov et al, 2004 ; Costa and Grybko, 2005 ). Indeed, marked morphological and functional changes have been detected in the GABAergic circuitries of both the cerebral cortex and the hippocampus of Ts65Dn mice ( Belichenko et al, 2009 ; Chakrabarti et al, 2010 ; Best et al, 2012 ; Martin et al, 2020 ). Therefore, this large body of evidence has now led to the notion that the excessive level of cortical inhibition is the major functional impairment in this DS model ( Best et al, 2007 ).…”
Section: Physical Exercise As a Potential Therapeutic Tool For Cns Pathologiesmentioning
confidence: 99%
“…Importantly, MC-PN inhibitory synapses were shown to use the α5-containing GABAAR (α5-GABAARs) (Ali and Thomson, 2008;Zorrilla de San Martin et al, 2020). Similarly, the hippocampal counterparts of MCs, the oriens-lacunoso moleculare (O-LM) interneurons express functional α5-GABAARs (Schulz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the actual synaptic circuits relying on the α5 subunit has important clinical implications. Indeed, α5-GABAARs were indicated as a prominent target for therapeutic interventions for cognitive dysfunctions in Down syndrome (Braudeau et al, 2011;Duchon et al, 2019;Schulz et al, 2019;Zorrilla de San Martin et al, 2020), depression (Zanos et al, 2017), anesthesia-induced memory impairment (Zurek et al, 2014) and schizophrenia (Duncan et al, 2010;Gill and Grace, 2014).…”
Section: Introductionmentioning
confidence: 99%